Constant market share analysis: A note - Graziella Bonanno (Economics and Econometrics Research Institute (EERI), 2016)
Constant Market Share Analysis (CMSA) is a method which decomposes the variation of market shares of any trader country. The more recent version is proposed by Fagerberg and Sollie (1985) that avoids some limits deriving from previously specifications. After explicating how CMSA works, this note presents some applications to the Italian case Two are the most important contribution of this paper. First, it includes a complete framework on CMSA. Second, the formal derivation of market share variation is proposed.
Keywords: C00; F00; 330; Market Share; Exports; Trade; Competitiveness; Decomposition